A survey on the cellular phone brand preference among UiTM Kota Kinabalu staff / Sylvin Eddie Ompison - Ompison, Sylvin Eddie (2006)
Cellular brand preferences among UiTM staff population is a research to identify the Universiti Teknologi MARA staff preferences and usage on cellular phone brand. Other than researching the demographic backgrounds and general cellular phones preferences of the respondents, this research mainly focuses to investigate whether there exists any relationship between the two. A series of questionnaires has been distributed to 150 respondents and the data from the survey is analyzed using Statically Package for Social Science (SPSS). In conclusion, there's a significant relationship between the respondent's monthly income with their phones expenditure and budget to buy cellular phones, and there's a significant relationship between marital status and their cellular phone expenditure. In the other hand, there are no significant relationship between ones profession and cellular phone brands, and there is no significant relationship between telecommunication service provider and cellular phone brand preferences.